IMPLEMENTASI PERATURAN DAERAH NOMOR 09 TAHUN 2011 TENTANG RETRIBUSI JASA USAHA PADA OBJEK WISATA DI KABUPATEN SIMALUNGUN - Sinaga, Gracy Insani; Hutahaean, Marlan; Rajagukguk, Jonson (Lembaga Kajian Ilmu Sosial dan Politik (LKISPOL), 2025)
This study discusses the Implementation of Regional Regulation Number 09 of 2011 concerning Business Service Retribution at tourist attractions in Simalungun Regency, with a focus on case studies in Dolok Pardamean District. The purpose of this study is to analyze the extent to which the regulation is implemented in the field, the obstacles faced, and its impact on the management and regional income from the tourism sector. The research method used is a qualitative approach with data collection techniques through interviews and documentation. The main informants in this study include government officials at the sub-district office, tourism object managers, and tourists. The results of the study indicate that the Implementation of Regional Regulation Number 09 of 2011 in Dolok Pardamean District has been carried out well. However, it still faces various challenges, such as lack of socialization to the community and tourism business actors, weak supervision of the implementation of levies, and obstacles in the collection and reporting system for retribution income. However, this policy has great potential in increasing regional original income (PAD) if implemented more optimally. In conclusion, efforts are needed to improve aspects of socialization, supervision, and transparency of the retribution system so that the implementation of this policy can run effectively and provide maximum benefits for local governments and the community.